Undermining environmental assessment laws: post-assessment amendments for mines in British Columbia, Canada, and potential impacts on water resources - Ben R. Collison; Patrick A. Reid; Hannah Dvorski; Mauricio J. Lopez; Alana R. Westwood; Nikki Skuce (FACETS, 2022)
In British Columbia (BC), Canada, there is increased attention on mines and their impacts on water resources. In BC, many proposed mines undergo provincial environmental assessment (EA), which predicts a mine’s risks and involves government oversight and public engagement. After approval, mines can apply for amendments that alter the project’s undertakings, including in ways that may harm water resources. We examined all amendment documents for mines undergoing provincial EA in BC from 2002 to 2020. Of the 23 approved mines, 15 (65%) requested a total of 49 amendments, of which 98% were approved. Most mines applied for their first amendment within 3 years of approval. We deemed 20 of the approved amendments (associated with 10 projects) likely to have negative impacts on water resources, including changes to effluent discharge, increased volume of water extraction, or degradation of fish habitat. Amendment applications and approval documents lacked specific, quantitative information to reinforce claims or decisions. We present the first known summary of EA amendments in any jurisdiction. Given that most mines in BC receive amendments, and many are related to water, we express concern that amendment processes increase risk to water resources without meeting standards of evidence and public scrutiny required by the regular EA process.